Analysis of National Security Risks in Indonesia's Three Trouble Spots as an Impact of the Development of BRI and FOIP in the Southeast Asian Region - Himam, Mohamad Faikhul; Suparno; Purnomo, Joko; Hadi Prasutiyon (PT FORMOSA CENDEKIA GLOBAL, 2024)
China is developing a Belt and Road Initiative (BRI) strategy to increase its geopolitical influence in the Southeast Asian region. The United States made the Free and Open Indo-Pacific America (FOIP) policy to offset China's geopolitical influence.This study aims to determine the national security risks that occur in 3 touble spots in Indonesia as a result of the development of BRI and FOIP in the Southeast Asian region. This study uses the Analytical Hierarchy Process (AHP) Method and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) approaches. Risk analysis on three Indonesian trouble spots shows that the area with the greatest risk is in the trouble spot 1 area (North Natuna Sea) with a value of 0.202 at level 1 very low. Meanwhile, the trouble spot 2 area (Ambalat) with a value of 0.040 is at level 1 very low and the trouble spot 3 area (Papua) with a value of 0.164 is at level 1 very low. This analysis shows that adjusting the weights and scores used in evaluating national security trouble spots can improve the decision-making process, as it shows the important role these factors play in risk ratings in each region